Musik Orkes Taman Bunga: Pandangan Antropologi Musik - Rizqa Gumilang; Sri Setyawati; Syahrizal Syahrizal; Ade Irwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explain the sustainability of Minang Orchestra music today, especially the Taman Bunga Orchestra group in West Sumatra Province. This research method uses a qualitative descriptive approach. Analysis from the perspective of Music Anthropology explains holistically about the sustainability of this group. Counter Hegemony as an analytical tool, what is the background to the selection of the Minang orchestra music genre and the sustainability of this group in facing the music industry. The results of the study show that there is a struggle between the ideology of this group and the market, especially the power of hegemony in the music industry market in Indonesia. The tenacity of its musical ideology is able to survive without disturbing or changing the form of its music. The principle of kinship is the main capital for the sustainability of this music group. The conclusion of this study is that the Taman Bunga Orchestra, also known as the Minang Orchestra, is a group of musicians who use traditional Minang music as the foundation of their music which is influenced by various elements such as rhythm, vocal techniques, and activities related to the event. Keyword: Counter Hegemony, Minang Orchestra Music, Musical Anthropology, Survival.